Restoring Brazilian savanna ground layer vegetation by topsoil and hay transfer - Lima Pilon, Natashi A. [UNESP]; Buisson, Elise; Durigan, Giselda (Wiley-Blackwell, 2018)
Tropical grassy biomes have been widely neglected for conservation and, after unplanned land use conversion, ecological restoration becomes urgent. The majority of interventions have been based on the misapplication of forest restoration techniques, because there are no validated techniques to restore the species-rich ground layer. In search for innovative techniques to restore the herbaceous layer of the cerrado vegetation, we carried out an experiment based upon topsoil and hay transfer, in the state of Sao Paulo, Brazil. The restoration treatments were: ( 1) transfer of topsoil collected at the end of the dry season; ( 2) topsoil collected at the end of the rainy season; ( 3) transfer of hay collected at the end of the dry season; ( 4) topsoil+hay collected at the end of the dry season; and ( 5) control. We used an old-growth grassland as source of material and as reference ecosystem to assess the efficacy of the restoration techniques applied to an area severely degraded after invasion by African grasses. After 211 days, hay transfer apparently inhibited germination and did not contribute to grassland vegetation recovery. Topsoil transfer, however, was effective at reintroducing herbaceous plants, including target species. The season of topsoil collection mattered: material collected at the end of the rainy season provided better results in terms of density and richness of the restored community than that from the dry season. The remaining challenge is to find sources of topsoil not invaded by exotic grasses in large enough amounts to support restoration initiatives without jeopardizing the source ecosystems.
Keywords: cerrado grassland; forbs; grasses; grassland restoration; nonforest ecosystems